Commodifying Renewable Energy Communication for Indonesia’a National Resilience - Nurdiansyah, Dian; Briandana, Rizki; Mohd Sofian, Muhammad Raqib; Relatani, Tantri (Jurnal Lemhannas RI, 2025)
Purpose: This study aims to analyse how renewable energy messages are visually constructed through social media and how this construction shapes the public's interpretations of the energy transition agenda within the framework of national resilience. Methodology: A descriptive qualitative approach, through virtual observation and content documentation, combined with multimodal discourse analysis (Kress & van Leeuwen) and reading of account performance metrics from the SNA (Social Network Analysis) platform in the form of a website, i.e., Socialblade. Findings: The messages related to renewable energy delivered have been implemented consistently in visual information, sustainability symbols, and simplification of policy narratives, thus shaping public perception and strengthening the legitimacy role of energy communication as part of national resilience. Originality: This study strengthens the understanding that digital visual communication contribute strategically to building socio-cultural and energy resilience by shaping public perceptions of the national energy transition.